Brightening of the global cloud field by nitric acid and the associated radiative forcing - Makkonen, R; Romakkaniemi, S; Kokkola, H; Stier, P; Raisanen, P; Rast, S; Feichter, J; Kulmala, M; Laaksonen, A (2012)
Clouds cool Earth's climate by reflecting 20% of the incoming solar energy, while also trapping part of the outgoing radiation. The effect of human activities on clouds is poorly understood, but the present-day anthropogenic cooling via changes of cloud albedo and lifetime could be of the same order as warming from anthropogenic addition in CO2. Soluble trace gases can increase water condensation to particles, possibly leading to activation of smaller aerosols and more numerous cloud droplets. We have studied the effect of nitric acid on the aerosol indirect effect with the global aerosol-climate model ECHAM5.5-HAM2. Including the nitric acid effect in the model increases cloud droplet number concentrations globally by 7%. The nitric acid contribution to the present-day cloud albedo effect was found to be-0.32 W m -2 and to the total indirect effect-0.46 W m -2. The contribution to the cloud albedo effect is shown to increase to-0.37 W m -2 by the year 2100, if considering only the reductions in available cloud condensation nuclei. Overall, the effect of nitric acid can play a large part in aerosol cooling during the following decades with decreasing SO2 emissions and increasing NOx and greenhouse gases. © 2012 Author(s).